SECRET: a secure and efficient certificate revocation scheme for mobile ad hoc networks - Mall, Dieynaba; Konaté, Karim; Pathan, Al-Sakib Khan (2014)
The intent of this paper is to propose an enhanced certificate revocation scheme for Mobile Ad hoc Networks (MANETs). Our approach is built on mainly two previously proposed mechanisms. A combination of the schemes and optimization of certain steps with intelligent choices of parameters could significantly reduce the overhead associated with such mechanism. We prove the efficiency of our approach by performance analysis. Also, we present the security analysis that shows clear gains than the previously proposed schemes.